Management of patients with end-stage renal disease: coronary artery bypass graft surgery versus percutaneous coronary intervention. (September 2018) - Karkhanis, Reena; Tam, Derrick Y.; Fremes, Stephen E.
Abstract : Purpose of review: Coronary artery disease is common in patients with end-stage renal disease (ESRD) on hemodialysis. ESRD patients are prone to atherosclerosis and are likely to present with advanced CAD requiring coronary artery bypass graft surgery (CABG) or percutaneous coronary intervention (PCI). Recent findings: Individual observational studies and aggregated results comparing PCI to CABG have shown an increased risk of early postoperative mortality in the CABG group followed by a decrease in late mortality and cardiovascular events. Drug eluting stents are preferred to bare metal stents in patients undergoing PCI. Bilateral versus single internal thoracic arterial grafting strategies showed no difference in survival, freedom from cardiac death or freedom from cardiac events. There was no clear survival advantage to off-pump CABG over on-pump CABG in ESRD patients. Evidence to support either CABG or PCI was limited to retrospective observational studies that were at risk for treatment allocation bias. Summary: CABG carries an upfront risk of increased perioperative mortality while demonstrating late survival benefit compared with PCI. Thus, in the context of balancing these competing risks and benefits, deciding on the most appropriate treatment in this high-risk cohort is challenging. Comprehensive patient evaluation by a multidisciplinary team is strongly recommended. Abstract : Supplemental Digital Content is available in the text